Service Quality, Training, and Development Mutual Support with Service Technology in Indonesia Private Companies - Ardiansyah, Tedy; Teruna, Dipa (Majalah Ilmiah Bijak, 2024)
In the technological era, every company is required to be able to serve its customers efficiently and quickly. However, not all services can be provided by technology. Because of this, companies are required to strike a strike a balance between humans (human touch) and technology. The aim of this research is to determine the relationship between informants and other informants for service quality, training, and development, to find out the model of informants using service quality, training, and development, and to find out comparisons. a one-industry model between banking and insurance for service quality and training and development. This is qualitative research with a phenomenological approach. Phenomenologists describe the main points of each informant's life experiences. Phenomenologists describe in detail from informants where the informants feel a phenomenon. The sample determined that four informants had expertise in their fields, as evidenced by their top positions in their companies. The analysis of this research was assisted by qualitative tools from Nvivo 12, and there is no doubt about international evidence, especially in data testing or analysis tests. The research instrument was adopted from previous research and assisted by theoretical studies to simplify and help determine policies for the company's after-sales service. The results obtained by three informants had strong and moderate relationship values for each informant included. The model obtained has novelty in the indicators, which gives rise to five indicators. Meanwhile, the comparison between banking and insurance informants is unique or novel in terms of gender, position, and type of company.